2021
DOI: 10.1111/jac.12488
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between drought and shade on the productivity of winter pea grown in a 25‐year‐old walnut‐based alley cropping system

Abstract: In the face of climate change, more frequent drought events are expected in the Mediterranean regions. Alley cropping is an agroforestry practice that represents a promising adaptation strategy to sustain yield productivity under drier conditions. However, the presence of trees limits the productivity of the intercrop by reducing light availability and by competing for soil water resources, which could potentially exacerbate the yield losses due to drought conditions. Furthermore, the effects of co‐occurring d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Earlier research has shown that herbage biomass in the close vicinity of trees is reduced due to competition for light, water and nutrients (Castillo et al, 2020; Ehret et al, 2018; Graß et al, 2020; Jose et al, 2004). Blanchet et al (2022) showed for a legume species in a Mediterranean alley cropping system that rainfall regime, but not light conditions, had an impact on the leaf area index. However, we did not find a consistent effect of the trees on biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that herbage biomass in the close vicinity of trees is reduced due to competition for light, water and nutrients (Castillo et al, 2020; Ehret et al, 2018; Graß et al, 2020; Jose et al, 2004). Blanchet et al (2022) showed for a legume species in a Mediterranean alley cropping system that rainfall regime, but not light conditions, had an impact on the leaf area index. However, we did not find a consistent effect of the trees on biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a slight delay in the phenological development of winter wheat and barley in the transition zone was observed, and plants remained small and developed grains with lower thousand grain and hectoliter weights compared with the control (data not shown, Lamerre, 2017). Several recent studies showed that tree shading can cause delayed maturity, negatively affect yield components and finally lead to reduced yields in field crops (e.g., Arenas‐Corraliza et al., 2020; Blanchet et al., 2021; Inurreta‐Aguirre et al., 2018; Qiao et al., 2020; Schmidt, Nendel, et al., 2019; Surki et al., 2020). For field‐to‐forest transition zones, simulations of Schmidt, Nendel, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mulching when planting c. walnut trees is an advisable practice to favour the production of quality timber, both for intercropped and non intercropped trees. Similar studies on intercropping of walnut trees were conducted in France and Spain [41,42], but on hybrid walnut trees (Juglans x intermedia Mj209xRa), which generally have a faster growth rate than c. walnut trees [30]. Those studies on walnut trees intercropping did not investigated on mulching.…”
Section: Trees Growthmentioning
confidence: 99%